Significance of extruded nuclear chromatin (regional nuclear shape malformation) in human spermatozoa: implications for ICSI - Mauri, A. L.; Oliveira, J. B. A. [UNESP]; Baruffi, R. L. R.; Petersen, C. G. [UNESP]; Vagnini, L. D.; Massaro, F. C.; Silva, L. F. I. [UNESP]; Nicoletti, A. P. M.; Franco, J. G. [UNESP] (Wiley-Blackwell, 2011)
The aim of this study was to determine the extent of DNA fragmentation and the presence of denatured single-strand or normal double-strand DNA in spermatozoa with extruded nuclear chromatin (ENC) selected by high magnification. Fresh semen samples from 55 patients were prepared by discontinuous isolate concentration gradient. Spermatozoa with normal nucleus (NN) and ENC were selected at 8400x magnification and placed on different slides. DNA fragmentation was determined by TUNEL assay. Denatured and double-stranded DNA was identified by the acridine orange fluorescence method. DNA fragmentation was not significantly different (p = 0.86) between spermatozoa with ENC (19.6%) and those with NN (20%). However, the percentage of spermatozoa with detectable denatured-stranded DNA in the ENC spermatozoon group (59.1%) was significantly higher (p < 0.0001) than in the NN group (44.9%). The high level of denatured DNA in spermatozoa with ENC suggests premature decondensation and disaggregation of sperm chromatin fibres. The results show an association between ENC and DNA damage in spermatozoa, and support the routine morphological selection and injection of motile spermatozoa at high-magnification intracytoplasmic sperm injection.
Keywords: DNA damage; DNA denaturation; DNA fragmentation; extruded nuclear chromatin; IMSI; MSOME